DNA barcoding reveals incorrect labelling of insects sold as food in the UK - Stefanos Siozios; Annie Massa; Catherine L. Parr; Rudi L. Verspoor; Gregory D.D. Hurst (PeerJ, 2020)
Background Insects form an established part of the diet in many parts of the world and insect food products are emerging into the European and North American marketplaces. Consumer confidence in product is key in developing this market, and accurate labelling of content identity is an important component of this. We used DNA barcoding to assess the accuracy of insect food products sold in the UK. Methods We purchased insects sold for human consumption from online retailers in the UK and compared the identity of the material ascertained from DNA barcoding to that stated on the product packaging. To this end, the COI sequence of mitochondrial DNA was amplified and sequenced, and compared the sequences produced to reference sequences in NCBI and the Barcode of Life Data System (BOLD). Results The barcode identity of all insects that were farmed was consistent with the packaging label. In contrast, disparity between barcode identity and package contents was revealed in two cases of foraged material (mopane worm and winged termites). One case of very broad family-level description was also highlighted, where material described as grasshopper was identified as Locusta migratoria from DNA barcode. Conclusion Overall these data indicate the need to establish tight protocols to validate product identity in this developing market. Maintaining biosafety and consumer confidence rely on accurate and consistent product labelling that provides a clear chain of information from producer to consumer.